Lessons learnt from the CERCA Project, a multicomponent intervention to promote adolescent sexual and reproductive health in three Latin America countries: a qualitative post-hoc evaluation. (October 2016) - Ivanova, Olena; Pozo, Kathya Cordova; Segura, Zoyla Esmeralda; Vega, Bernardo; Chandra-Mouli, Venkatraman; Hindin, Michelle J.; Temmerman, Marleen; Decat, Peter; De Meyer, Sara; Michielsen, Kristien
Highlights: Large projects like CERCA require a preparatory phase and a thorough analysis of the situation at the country level as well as community-specific context information, to which sufficient time and budget should be attributed. An essential part of community-based intervention and action research is to adapt the monitoring strategy if the interventions are changed and to thoroughly document all activities. Accepting teenage pregnancies as a complex issue, not only means adapting interventions to this complexity, but also the evaluation design. In the case of the CERCA Project an overall evaluation should have included a component for each activity. Further, the evaluation rightly addressed the effectiveness of the intervention package but should have extended this to address their acceptability, and factors that helped or hindered their application among all target groups and other stakeholders. Through the concerted application of a multi-faceted strategy, it is possible to decrease the taboo on adolescent sexuality in a conservative setting. Abstract: The Community-Embedded Reproductive Health Care for Adolescents (CERCA) Project was implemented in Bolivia, Ecuador and Nicaragua (2011–2014) to test the effectiveness of interventions preventing teenage pregnancies. As the outcome evaluation showed limited impact, a post-hoc process evaluation was carried out to determine if and how CERCA's design, implementation, monitoring and evaluation affected the results. We did a document analysis and conducted 18 in-depth interviews and 21 focus group discussions with stakeholders and beneficiaries. Transcripts were analyzed using directed content analysis. Data showed that CERCA sensitized stakeholders and encouraged the discussion on this sensitive issue. In terms of design, a strong point was the participatory approach; a weak point was that the detailed situation analysis was completed too late. In terms of implementation, a strong point was that multifaceted activities were implemented; a weak point was that the activities were not pilot tested for feasibility/acceptability and evolved substantially throughout the Project. In terms of monitoring, strong points were that regular monitoring kept the Project on track administratively/financially; a weak point was that monitoring indicators did not change as the intervention package changed. In terms of evaluation, weak points were the substantial attrition rate and narrow focus on adolescents. This study provides recommendations for future projects.